Letter : Help for the Workers of Spain Fund - Marchbank, John
028-0174-001 TELEGRAMS: "BEWARE, NORWEST, LONDON." TELEPHONE: EUSTON 4771, 5 LINES. The National Union of Railwaymen. Unity House, Euston Road, London, N.W.1. J. MARCHBANK, GENERAL SECRETARY. C. W. BROWN, ASSISTANT GENERAL SECRETARY. Your Ref: HVT/FC/30. In Your Reply Refer To: F.M.A.2. 12th October, 1936. Mr. H. V. Tewson, National Council of Labour, Transport House, Smith Square, S.W.1. Dear Mr. Tewson, HELP FOR THE SPANISH WORKERS. With further reference to my letter of the 24th ultimo I shall be pleased to know if more definite information is now available, and if you can favour me with full details of the position. Yours faithfully, J. Marchbank 292/946/28/174